Pelatihan Kelompok Petani Perempuan Desa Kaduara Timur melalui Diversifikasi Olahan Singkong - Iswahyudi; Marchel Putra Garfansa (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
East Kaduara Village is one of the villages in Pragaan Madura District with the majority of residents working as farmers. The potential commodity in the village is the cassava plant. Farmers generally sell the cassava directly without having to go through a processing process first. Post-harvest processing technology and diversification of processed products made from cassava that have not been implemented have caused the cassava harvest to pile up and have a low selling value, so it needs to be socialized and developed together. This program aims to provide knowledge and skills in processing cassava as a business product for farmwomens in East Kaduara Village. It is also hoped that the processed products resulting from the service can become a mainstay product and characteristic of East Kaduara Village. Service activities consist of providing materials and training followed by distributing questionnaires to measure the level of achievement of the socialization and training carried out. The results showed an increase in participants' skills, insight and productivity regarding the processed and packaged of cassava chips. The results of the observations showed an increase in the participants' skills and insight regarding the processed and packaged of cassava chips. The results of the participants' assessment on the training showed an increase in skills and insight with an average percentage of 75%. Participants showed activity and creativity that fell into the excellent category and enthusiasm which demonstrat in the activeness of the participants asking questions and expressed their ideas in designing packaging label designs and managed cassava chips. Processed chip products also received a positive response from more than 70% of consumer respondents who indicated the product had a selling value.